2014
DOI: 10.1212/01.wnl.0000457072.94144.8f
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde dehydrogenase variation enhances effect of pesticides associated with Parkinson disease

Abstract: Objective: The objective of this study was to determine whether environmental and genetic alterations of neuronal aldehyde dehydrogenase (ALDH) enzymes were associated with increased Parkinson disease (PD) risk in an epidemiologic study.Methods: A novel ex vivo assay was developed to identify pesticides that can inhibit neuronal ALDH activity. These were investigated for PD associations in a population-based case-control study, the Parkinson's Environment & Genes (PEG) Study. Common variants in the mitochondri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In 2014, Fitzmaurice et al concluded that individuals who expressed a variant of the ALDH2 and ALDH2 genes 159 were associated with exacerbated PD risk when exposed to ALDH-inhibiting compounds, 67 However, benomyl bioaccumulates within tissues, and workers exposed to benomyl at multiple work and home locations had an increased PD risk than exposure at just one location. The link between benomyl exposure and PD was attributed to alteration of DA homeostasis and ALDH inhibition 70 (Scheme 5.1).…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, Fitzmaurice et al concluded that individuals who expressed a variant of the ALDH2 and ALDH2 genes 159 were associated with exacerbated PD risk when exposed to ALDH-inhibiting compounds, 67 However, benomyl bioaccumulates within tissues, and workers exposed to benomyl at multiple work and home locations had an increased PD risk than exposure at just one location. The link between benomyl exposure and PD was attributed to alteration of DA homeostasis and ALDH inhibition 70 (Scheme 5.1).…”
Section: Discussionmentioning
confidence: 99%